ISOLATION AND IDENTIFICATION OF LACTIC ACID PRODUCING BACTERIA FROM CAMEL MILK - Toqeer Ahmad, Rashida Kanwal, Izhar Hussain Athar1, Najam Ayub (Pakistan Veterinary Journal, 2002)
Lactic acid bacteria (LAB) were isolated from camel milk by culturing the camel milk on specific media and pure culture was obtained by sub culturing. Purification of culture was confirmed by Gram's staining and identified by different bio-chemical tests. Camel milk contains lactic acid producing bacteria including Strpptococci such as S. cremoris and S. lactis and Lactobacilli such as L. acidophilus L. acidophilus grows more rapidly in camel milk than others as its growth is supported by camel milk. A variety of food can be preserved by lactic acid fermentation, so starter culture was prepared from strains which were isolated from camel milk. Camel and buffalo's milk cheese was prepared by using starter culture. The strains isolated from camel milk were best for acid production and can coagulate the milk in less lime. Camel milk cheese was prepared and compared with buffalo's milk cheese. It is concluded that cheese can be prepared successfully from camel milk and better results can be obtained by coagulating milk with starter culture.